"Debunking" and the short story: Coover´s challenge to authorities in "The brother" - Meyers Skredsvig, Kari (2015)
En este trabajo se discuten las maneras en que el autor de "The Brother", Robert Coover, se apodera de la forma del cuento con el fin de retar las convenciones teóricas y críticas del género, además de las expectativas y las suposiciones de los lectores en el proceso de construcción de significado. The following discussion examines the ways in which Robert Coover appropriates the short story form in "The Brother" to challenge not only theoretical and critical conventions of that genre, but also readers' expectations and assumptions in the process of constructing meaning.